Market Reaction to the Announcement of the Launch of International Carbon Trading in Companies Indexed by IDXESG Leaders on the Indonesia Stock Exchange - Aldiyanto Haseng; Selvi Selvi; Dewi Indrayani Hamin (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to identify the market reaction triggered by the information contained in the event of the launch of international carbon trading by IDXCarbon, particularly for companies listed in the IDXESG Leaders index on the Indonesia Stock Exchange. The data used in this study are secondary data obtained through the documentation method of individual historical stock prices. The sample consists of 30 companies indexed in IDXESG Leaders. The method used is an event study with abnormal return analysis, followed by a paired sample t-test and Wilcoxon signed rank test using SPSS 25. Based on the result, the paired sample t-test shows that the launch of international carbon trading by IDXCarbon does not indicate a significant difference in abnormal return before and after the event. However, the Wilcoxon signed rank test shows a dominance of positive reactions, indicating that the event carries favorable information (good news).